The Art of C.Y.A.: Documentation for Department Chairs - Christopher Barrick (Academic Chairpersons Conference Proceedings, 2017)
From day one, department chairs are instructed to keep good records and “document, document, document.” But what does proper documentation look like? Through the use of memos for record and other means, learn to document in a meaningful and useful manner so that you have really practiced “C.Y.A.”
Keywords: documentation; record keeping; records; CYA; memos